The Influence of Translation Technique on Translation Ideology in the Novel - Supatmiwati, Diah; Anggara, Gde Wetan Pragena; Syahid, Agus (Humanitatis : Journal of Language and Literature, 2024)
Translation is extremely crucial when communicating information, culture, messages, and so on between two or more people who speak different languages. The problem arises when it comes to translate a fantasy stories or games because the translation technique and ideology are heavily relied on the culture. This research aims to find out the influence of translation technique on ideology in translating the novel â€œOverlordâ€. This method of this research is qualitative, and the data collected is used to determine the analytical unit, which is the fantasy novel "Overlord". The unit is then broken into smaller parts, which correspond to the fantasy and gaming terms. Following that, a data sample is drawn from chapters one through five of the novels before removing unneeded and irrelevant data for this study. The data were analyzed based on Mile and Huberman techniques; data condensation, display, verification, and concluding. The findings of this research are the use of 7 translation techniques, which are: discursive creation (60), established equivalent (15), borrowing (184), Amplification (9), literal translation (118), modulation (29), and Particularization (4), and the most used translation technique is borrowing (184) and literal translation (118) in the novel. This means that the translation ideology that is used is foreignization which means that the translation is oriented to the source language culture.